2006
DOI: 10.1073/pnas.0601971103
|View full text |Cite
|
Sign up to set email alerts
|

Discrete steps in sensing of β-lactam antibiotics by the BlaR1 protein of the methicillin-resistant Staphylococcus aureus bacterium

Abstract: Chemical sensing by cell-surface receptors to effect signal transduction is a ubiquitous biological event. Despite extensive structural biochemical study, detailed knowledge of how signal transduction occurs is largely lacking. We report herein a kinetic and receptor ͉ signal transduction ͉ infrared spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 24 publications
2
56
0
Order By: Relevance
“…As class D ␤-lactamases enjoy symmetry in catalysis (42), N-carboxylated lysine promotes/activates a water molecule for the deacylation event as well, a function that BlaR1 is incapable of performing as it experiences N-decarboxylation on acylation by the antibiotic. It is known that the N-decarboxylated Lys-392 of BlaR1 is incapable of promoting the deacylation step (8). However, our simulations of the dynamics of the BlaR1 sensor domain showed that N-carboxylated Lys-392 is well poised to promote acylation of Ser-389 only after it assumes a conformation that closely approximates that of the class D ␤-lactamase.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…As class D ␤-lactamases enjoy symmetry in catalysis (42), N-carboxylated lysine promotes/activates a water molecule for the deacylation event as well, a function that BlaR1 is incapable of performing as it experiences N-decarboxylation on acylation by the antibiotic. It is known that the N-decarboxylated Lys-392 of BlaR1 is incapable of promoting the deacylation step (8). However, our simulations of the dynamics of the BlaR1 sensor domain showed that N-carboxylated Lys-392 is well poised to promote acylation of Ser-389 only after it assumes a conformation that closely approximates that of the class D ␤-lactamase.…”
Section: Discussionmentioning
confidence: 68%
“…The protein with the unmodified Lys-392 is not active, as disclosed in an earlier study (8). Lys-392 has rotated nearly 180°about its ␦ carbon in the protein molecule with N-carboxylated lysine.…”
Section: Structure Of the Native Blarmentioning
confidence: 78%
See 1 more Smart Citation
“…Its role as a ␤-lactam sensor/signal transducer is fully appreciated, but the details of its molecular events are less understood. The process of ␤-lactam sensing is elaborate, and it involves an uncommon N-carboxylated lysine that experiences N-decarboxylation on acylation of the protein with the antibiotic (2,4). This N-decarboxylation of the lysine within the antibiotic-binding site affords longevity to the acyl-protein species, which in turn initiates signaling events from the surface of the membrane to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…1). Antibiotic acylates the C-terminal sensor domain located on the surface of the plasma membrane by a mechanism involving a surface loop of the protein (1) and an elaborate process that leads to N-decarboxylation of a lysine within the antibiotic-binding site (2)(3)(4). The acylated species enjoys a longevity that often exceeds the doubling time of most S. aureus strains; hence, a single BlaR1 modification by the antibiotic is sufficient for the entire bacterial generation (5).…”
mentioning
confidence: 99%